Nurses Staff Knowledge Regarding Standard Hand Hygiene Precautions in Rania City/Kurdistan Regional Government of Iraq - Blend B. Ameen (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: -To assess nurses staff level of knowledge regarding standard hand hygiene precaution, and to find out the association between their level of knowledge and some of socio-demographic characteristics such as (gender, and level of education). Method: Quantitative design, a descriptive study was carried out at Rania City. To achieve the objectives of the present study, non-probability purposive sample was used. The study sample was (66) nurses who were providing nursing services at two hospitals (Rania teaching hospital and Rania maternity and pediatric hospital). 10 of samples were excluded for a pilot study. A questionnaire was constructed by the researcher for the purpose of the study technique and it was used as a tool for data collection. The data were collected through using an interview technique (face to face) approach.. Data were analyzed through the application of descriptive statistical analysis, such as: (frequency, percentage, mean of scores), and inferential statistical analysis (Pearson’s chi-square and correlation coefficient), by using the statistical package of social sciences (SPSS) version (20). Results: The study indicated that the most of samples aged between 32-36 years old and represents 28.6% of the study samples. In addition, the highest percentages of the nursing staffs were female 73%. Concerning of the educational level, more than half of nurses graduated from the medical institute 66 %. And the largest study sample have 6-10 years of experiences 28.5%The findings of the study reveal that the nurses have a good level of knowledge about hand hygiene (HH) and appropriate time to do HH. The majority of the stay sample routinely used HH and they disinfectant their hands either by washing hands with water and soap or use alcohol-based jell for, while some of the nurses don’t wash their hands either because they are busy, they forget to do it or even the products are not available or not easy to reach. The study also approves that there was a statistically no significant association between the knowledge of nurses and gender and years of experiences.